An assessment of sub-standard water pressure in South African potable distribution systems - Strijdom, Louis; Speight, Vanessa; Jacobs, Heinz Erasmus (Journal of water, sanitation, and hygiene for development, 2017)
Sub-standard residual water pressures in urban water distribution systems (WDS) are a prevalent phenomenon in developing countries – South Africa being no exception. The phenomenon of sub-standard pressure is poorly understood, with intermittent supply ultimately resulting when there is no residual pressure left in the system. This research addressed the prevalence and extent of sub-standard pressures by using hydraulic models of potable WDS for 71 South African towns, located in 17 different South African municipalities geographically spread over the country. The hydraulic models included 539,388 modelled nodes, which were analysed to determine the number of nodes with sub-standard pressure heads during peak hour flow conditions. The results show that the residual pressure head was <24 m at 16.5% of the model nodes under peak hour flow conditions, with 6.7% of the nodes having pressure heads <12 m. In contrast, the results also report relatively high pressures in certain parts of the systems, far in excess of the minimum requirement, underlining the need for better pressure management at both high and low ranges. It was also noted that the South African design criterion is relatively stringent compared with some other countries and could potentially be relaxed in future.